On the Religious and Legal Significance of the Consummation of Marriage - K. V. Karpenko (Vestnik MGIMO-Universiteta)
The article is devoted to this little-studied problem in modern family law as the consummation of marriage. The author analyzes the role and importance of this legal phenomenon in the various religious and legal systems, starting from old Aryan Vedas and ending with the current legislation of several contemporary states. The author arrives to the conclusion that the consummation of marriage has not lost its relevance in the modern family law and still serves as a legal fact, which generates important consequences for the marital relationship.